2017
DOI: 10.1021/acsami.7b01229
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Crumpled Graphene-Based Nanosheets with Ultrahigh NO2 Gas Sensibility

Abstract: It is well-established that the structures dominate the properties. Inspired by the highly contorted and crumpled maxilloturbinate inside dog nose, herein an artificial nanostructure, i.e., 3D crumpled graphene-based nanosheets, is reported with the simple fabrication, detailed characterizations, and efficient gas-sensing applications. A facile supramolecular noncovalent assembly is introduced to modify graphene with functional molecules, followed with a lyophilization process to massively transform 2D plane g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 48 publications
(58 reference statements)
1
71
0
Order By: Relevance
“…The literature reveals that metal-oxide materials are the most widely used scaffold to fabricate gas sensors [15][16][17][18][19][20]. In particular, metal-oxide materials are widely utilized to fabricate sensors for toxic and explosive gases [20][21][22][23][24]. It has been observed that the nanocrystal interfaces can significantly influence the optical and electrical properties and charge-trapping phenomena [22][23][24][25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reveals that metal-oxide materials are the most widely used scaffold to fabricate gas sensors [15][16][17][18][19][20]. In particular, metal-oxide materials are widely utilized to fabricate sensors for toxic and explosive gases [20][21][22][23][24]. It has been observed that the nanocrystal interfaces can significantly influence the optical and electrical properties and charge-trapping phenomena [22][23][24][25].…”
mentioning
confidence: 99%
“…In particular, metal-oxide materials are widely utilized to fabricate sensors for toxic and explosive gases [20][21][22][23][24]. It has been observed that the nanocrystal interfaces can significantly influence the optical and electrical properties and charge-trapping phenomena [22][23][24][25]. Zinc oxide (ZnO) is one of the most important and functional materials because of its various significant properties, including its wide bandgap; high exciton binding energy, piezoelectricity, and pyroelectricity; high conductivity and electron mobility; good stability in chemical and thermal environments; and biocompatibility [26][27][28].…”
mentioning
confidence: 99%
“…2a), resulting in the loss of the interlaminar surface area and nally a largely reduced gas response. 30 While 4HQ-rGO uniformly deposited on the IDEs (Fig. 2b) due to its excellent dispersibility in water, 31 a higher specic surface area and better sensing performance were generated.…”
Section: Resultsmentioning
confidence: 99%
“…In order to make the interior sheet fully contact to the test gas, it is necessary to prepared micro-nano hierarchical structure on the film to expand the specific surface area of material, and then, to improve the performance of the device. Researchers have developed nanostructured materials such as a 3-dimensional (3D) graphene foam network and a graphene nanomesh to overcome low-level sensitivity and slow response of graphene-based gas sensors 19 – 23 . Han et al .…”
Section: Introductionmentioning
confidence: 99%